A Simple Isomerization of the Purine Scaffold of a Kinase Inhibitor, Roscovitine, Affords a Four- to Seven-Fold Enhancement of Its Affinity for Four CDKs. Could This Be Traced Back to Conjugation-Induced Stiffenings/Loosenings of Rotational Barriers? - El Hage, Krystel (ACS Omega, 2017)
[Image: see text] Roscovitine is an antitumor purine inhibitor of cyclin-dependent kinase CDK5, for which it displays submicromolar affinity. It reached phase IIb clinical trials in 2007. The search for analogues with improved kinase affinities led recently to an isomer, finisterine, having a nearly 10-fold greater affinity for both CDK5 and CDK9. It solely differs by the displacement of one nitrogen atom in the purine ring, from position 6 to position 9. This has no incidence on the intermolecular interaction of either drug with the neighboring sites that anchor the ring in the recognition site. Quantum chemistry calculations combined with conformational and topological analyses of the impact of the purine ring isomerization of roscovitine and finisterine on its conformational stability show that the modified electronic conjugation, on the other hand, results in a stiffening of the rotational barrier around the extracyclic C–NH bond of finisterine, vicinal to N9, and to which an aryl ring is connected, along with a loosening of the barrier around an extracyclic C6–C bond connecting to a shorter, hydrophobic arm. The first effect is proposed to lead to a lesser hydration entropy of solvation in the case of finisterine, thus to a facilitated desolvation term in the overall energy balances.